2023
DOI: 10.2147/ijgm.s404813
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous Pathogenic and Likely Pathogenic Symptomatic HTRA1 Variant Carriers in Cerebral Small Vessel Disease

Abstract: High temperature requirement serine peptidase A1 (HTRA1) related cerebral small vessel disease (CSVD) includes both symptomatic heterozygous HTRA1 variant carrier and cerebral autosomal recessive arteriopathy with subcortical infarcts and leukoencephalopathy (CARASIL) patients. Presently, most reported symptomatic heterozygous HTRA1 variant carrier cases are sporadic family reports with a lack of specific characteristics. Additionally, the molecular mechanism of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…However, contradictory evidence has emerged suggesting that HTRA1 protease can increase TGF-β release and signaling (Beaufort et al, 2014). It has been suggested that TGF-β participates in various pathogenic mechanisms in CARASIL (Xu et al, 2023;Yamamoto & Ihara, 2017), while the precise role of TGF-β in heterozygous HTRA1-related disease requires further investigation.…”
Section: Htra1 Gene: Structure and Functionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, contradictory evidence has emerged suggesting that HTRA1 protease can increase TGF-β release and signaling (Beaufort et al, 2014). It has been suggested that TGF-β participates in various pathogenic mechanisms in CARASIL (Xu et al, 2023;Yamamoto & Ihara, 2017), while the precise role of TGF-β in heterozygous HTRA1-related disease requires further investigation.…”
Section: Htra1 Gene: Structure and Functionmentioning
confidence: 99%
“…Clinical manifestations of HTRA1-autosomal dominant disease include stroke, cognitive decline, gait disorders, psychiatric disorders, alopecia, migraine, and spine disorders. The first symptom of onset is mostly stroke (45%) (Xu et al, 2023). Extra-neurological features are less common, with spine disorders present in 47.27% and alopecia in 20% of cases.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 2 more Smart Citations